EDUKASI PENERAPAN SANITASI DAN HIGIENE PADA UMKM OLAHAN HASIL PERIKANAN DI KECAMATAN KWANDANG - Wila Rumina Nento; Shindy Hamidah Manteu; Sitty Ainsyah Habibie (Universitas Mataram, 2023)
Kwandang District has abundant fisheries resource potential. Therefore, it is necessary for the fisheries processing process to increase local community income to support the economy of the community in Kwandang District by utilizing Micro, Small and Medium Enterprises (MSMEs). The problem in society is that there is still a lack of experience in implementing sanitation and hygiene in MSMEs, such as sanitation and hygiene of raw materials, employees, facilities, infrastructure, products, final products, mutual contamination, and handling of the waste produced. The aim of this activity is to increase knowledge regarding good production methods by implementing correct sanitation and hygiene and creating quality products that are liked by the public that meet product quality standards. The method used consists of 3 stages. The first stage is conducting surveys and collecting data on the distribution of groups of MSME actors, the second stage is educational activities by providing material on sanitation and hygiene and the third stage is training on fishery product processing. The results of location observations show that there are 5 groups of fisheries processing MSMEs in Katialada Village, Kwandang District, and with socialization/counseling activities they can provide information to business actors regarding the importance of implementing sanitation and hygiene related to all processing facilities, cleaning facilities, personnel and the environment in the Processing Unit Fish (UPI). In addition, training was carried out by demonstrating frozen ebi furry shrimp processing techniques. Conclusion Educational activities with material on the application of sanitation and hygiene as well as fisheries processing techniques can increase the knowledge and skills of business actors. Implementing good and correct sanitation and hygiene in MSMEs can produce standard quality products that comply with Indonesian National Standards (SNI) and can expand marketing.